Tailored BEST Exercise Protocol in Heart Failure Rehabilitation - Kevin Triangto; Basuni Radi; Bambang Budi Siswanto; Tresia Fransiska Ulianna Tambunan; Teuku Heriansyah; Alida Rosita Harahap; Aria Kekalih; Ade Meidian Ambari; Bambang Dwiputra; Dwita Rian Desandri; Hajime Katsukawa; Anwar Santoso (Majalah Kardiologi Indonesia)
Introduction